The Development of Science Teaching Materials Based on the PjBL-STEM Model and ESD Approach on Environmental Pollution Materials - Yeni Setyowati*; Ida Kaniawati; Siti Sriyati; Elah Nurlaelah; Hernani Hernani (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Critical thinking skills and sustainability consciousness are competencies that students need to have to face the challenges of the 21st century and can be developed through appropriate learning activities and teaching materials. Unfortunately, teachers do not have the right guidelines and teaching materials to implement learning activities that develop those competencies. This study aims to develop science teaching materials with the PjBL-STEM learning model and education for sustainable development (ESD) approach on environmental pollution material to enhance critical thinking skill and sustainability consciousness of junior high school student in class VII. The teaching materials developed in this study are Lesson Plans, Worksheets, and assessment for critical thinking skill and sustainability consciousness. The research method used in developing the product is research and development (R D). While the RD research model used is the four-D development model. The four-D development model has several stage, namely define, design, develop, and disseminate. This study solely reached the development stage. The feasibility test was carried out by the experts. The data were analized using percentage of the product eligibility in the validation form. Based on the results of the feasibility validation, the critical thinking skill asessment validation received a percentage value of 85% with very feasible criteria and sustainability consciousness asessment validation received a percentage value of  97% with very feasible criteria. The finding of the research indicate that the teaching material developed is valid and eligible to use.